ANALISIS PENGARUH KEPUTUSAN INVESTASI, PENDANAAN, DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PT. ASTRA INTERNATIONAL TBK - Haida Aritonang; Purwanti (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
The value of a company is one of the aspects that every company should pay attention to in order to maintain financial performance stability. A company is a place where an organization conducts its business to produce goods and services. This research focuses on company value, with investment decisions, financing decisions, and dividend policies being influencing factors. The objective of this research is to explain and analyze the impact of investment decisions, financing decisions, and dividend policies on company value. The population used in this research is the financial performance of Astra International Tbk. The researcher's sample consists of the consolidated financial statements of PT. Astra International Tbk from 2013 to 2022, obtained through the website www.astra.co.id. The sampling method employed is the time series method. The data processing method used by the researcher in this study is multiple linear regression analysis (LS) using Eviews 12. The findings of this research can be summarized as follows: investment decisions do not significantly influence company value, while financing decisions and dividend policies significantly affect company value. Simultaneously, it is known that investment decisions, financing decisions, and dividend policies collectively have a significant impact on company value. The coefficient of determination is found to be 98.63%.